Optimizing Risk in the Aluminium Industry Applied to Misr Aluminium Company - Ismail, Mohamed; Mohamed, Marwan (The Arab Journal of Administration, 2024)
The process of risk discovery and analysis is necessary to maintain the stability of the aluminium industry and all industries dependent on it in Egypt. But often the results of the risks to which this industry is exposed are a complete loss, so rejected by insurance and reinsurance companies, or they are over-evaluated and priced at a price close to their value if they are accepted, Therefore, it was very important to search for methods through which to reduce the degree of risk, Until the risk becomes good and easy to cover, and it is accepted at a low cost due to the low probability of its occurrence, and the control of losses in the event of the occurrence of the risk. The study aimed to help the company to compete internally and externally and to strengthen its financial position, as reducing the degree of risk leads to improving the financial results of the company. This is done by finding the best method that can be followed to manage the risks of the company. The researchers collected the data needed through conducting personal interviews in the company. Analytic Hierarchy Process (AHP) method was used in the study. It was concluded that commercial insurance is the best method that can be followed to manage the risks of the studied company. The researchers recommended following the method of prevention and control to convert the risk from bad to good according to the model proposed for the study, until the commercial insurance against the company’s risks is accepted with appropriate cost.